Proposed upgrading of Ipoh General Post Office for POS Malaysia Berhad at Jalan Panglima Bukit Gantang Wahab, 30670 Ipoh, Perak Darul Ridzuan / Nadia Azira Sha'ari - Sha'ari, Nadia Azira (Faculty of Architecture, Planning and Surveying, 2011)
Pos Malaysia Berhad is the company which is experienced for 175 years in Malaysia in mail services. Unfortunately the scenario at all the post office in Malaysia is not in line with the modernity that Malaysia has nowadays. Most post office looks are dull, with old furniture and not welcome people to deals with them. Realizing the situation, Pos Malaysia Berhad currently trying to fulfil their Business Transformation Plan by providing the quality of their systems, services, products, facilities and also business strategies. One of the plans is upgrading their headquarters office and every general post office in every state. Related to PMB transformation plan, I take the opportunity to propose upgrading of Ipoh General Post Office at Jalan Panglima Bukit Gantang Wahab, 30670 Ipoh, Perak Darul Ridzuan. In order to upgrading the building into a new and modern look, services provided and traffic flow in the post office must been studied clearly. It could not become the same design as an existing but must be more modern look, complete with great facilities and userfriendly also must be green design as we have to protect our planet. With this upgrading project, Pos Malaysia Berhad can compete positively and maintain its position as largest provider of mail services in Malaysia.